دور المرأة المسلمة في مكافحة ظاهرة التَّنَمُّر وآثاره في المجتمعات المعاصرة "دراسة تربوية اجتماعية شرعية ": The Role of Muslim Women in Combating Bullying and its Effects in Contemporary Societies “An Educational, Social and Legal study” - Salihu Musa Jibo Muhammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تُعَدُّ ظاهرة التَّنَمُّر في العصر الراهن من المشكلات التي تُحدِثُ رُعْباً وقلقاً لدى الطلبة الصِّغار والمراهقين، وأضْحَتْ من الظواهر الأكثر انتشاراً في العصر الحاضر، والتي تَبْعَثُ في طياتها سموماً فتاكةً في الأسرة والمدرسة والمجتمع بمختلف انتماءاته، حيث يترك أثراً سَيِّئاً في نفوس المتنمَّر عليهم – الضحية- والمتنمِّر نفسه، وذلك لإحداث مشكلات نفسية وبدنية مقلقة؛ لأنَّها باتت تخلق خطراً محدقًا في المدارس وخارجها، وتطوَّرت الظاهرة كغيرها من الظواهر النفسية إلى التَّنَمُّر الإلكتروني الذي برز في الآونة الأخيرة بسبب التطورات الهائلة للعالم. وقد هدفت هذه الدراسة إلى إبراز الدور الذي يمكن للمرأة المسلمة القيام به تُجاه هذه الظاهرة من أجل مكافحتها من مراحلها الأولى؛ عن طريق الوقاية المـــُــسْبقة، لِمَا لها من شأنٍ عظيم في الإسلام. وما للشريعة الإسلامية من الدور الفاعل في اجتثاث مثل هذه الظاهرة وقمعها، باتباع منهج سوي منبثق من الكتاب والسنة النبوية الشريفة، والمناهج المستخدمة لتحقيق هذه الدراسة هما: المنهج الوصفي والمنهج الاستقرائي. وقد برزت بعض النتائج المهمة للدراسة منها: أنَّ الدراسة أسفرت أنَّ التَّنَمُّر ليس مجرد مشكلة؛ وإنما تفاقم أمرُه إلى كونه ظاهرة اجتماعية تربوية كبيرة تنتشر في جميع أنحاء العالم، وأن أكثر البقع عرضة لظاهرة التَّنَمُّر هي المدرسة، وأن أسباب انتشار ظاهرة التنمر تعود إلى أسباب شخصية، ونفسية، واجتماعية، ومدرسية. كما أثبتت الدراسة أن للمرأة دوراً كبيراً في مكافحة هذه الظاهرة من خلال التعامل معها في مراحلها الأولى عن طريق الكشف عن ضحايا التَّنَمُّر، ووضع قواعد لمكافحته عن طريق الوقاية المسبقة، والخطوات العلاجية المتلاحقة، وعنيت الدراسة بعرض حلول شرعية من القرآن والسنة لهذه الظاهرة. Abstract The phenomenon of bullying in the current era is one of the problems that cause fear and anxiety among young students and adolescents, and it has become one of the most prevalent phenomena in the present era, which sends deadly toxins into the family, school and society of its various affiliations, leaving its impact on the victims of their various affiliations. the bully himself, in order to cause disturbing psychological and physical problems; Because it is creating an imminent danger in schools and outside it, , and the phenomenon has developed, like other psychological phenomena, to electronic bullying that has emerged in recent times due to the huge developments in the world. This study aimed to highlight the role that Muslim women can play towards this phenomenon in order to combat it from its early stages, through pre-prevention, because of its great importance in Islam. And what is the Islamic Sharia effective role in eradicating and suppressing such a phenomenon, by following a normal approach emanating from the Holy Quran and Sunnah, The methods used to achieve this study are: the descriptive approach and the inductive approach. Some important findings of the study emerged, including that: The bullying is not just a problem; Rather, it aggravated to the fact that it is a large social and educational phenomenon that spreads all over the world, and that the schools are the most vulnerable to bullying, and that the causes of the spread of bullying are due to personal, psychological, social, and school reasons. The study also proved that women have a major role in combating this phenomenon by dealing with it in its early stages by revealing the victims of bullying, and setting rules to combat it through prior prevention, and successive remedial steps from the Qur’an and Sunnah.